Effects of creatine supplementation and resistance training on muscle strength and weightlifting performance - Rawson, E. S.; Volek, J. S. (The Journal of Strength and Conditioning Research, 2003)
Creatine monohydrate has become the supplement of choice for many athletes striving to improve sports performance. Recent data indicate that athletes may not be using creatine as a sports performance booster per se but instead use creatine chronically as a training aid to augment intense resistance training workouts. Although several studies have evaluated the combined effects of creatine supplementation and resistance training on muscle strength and weightlifting performance, these data have not been analyzed collectively. The purpose of this review is to evaluate the effects of creatine supplementation on muscle strength and weightlifting performance when ingested concomitant with resistance training. The effects of gender, interindividual variability, training status, and possible mechanisms of action are discussed. Of the 22 studies reviewed, the average increase in muscle strength (1, 3, or 10 repetition maximum [RM]) following creatine supplementation plus resistance training was 8% greater than the average increase in muscle strength following placebo ingestion during resistance training (20 vs. 12%). Similarly, the average increase in weightlifting performance (maximal repetitions at a given percent of maximal strength) following creatine supplementation plus resistance training was 14% greater than the average increase in weightlifting performance following placebo ingestion during resistance training (26 vs. 12%). The increase in bench press 1RM ranged from 3 to 45%, and the improvement in weightlifting performance in the bench press ranged from 16 to 43%. Thus there is substantial evidence to indicate that creatine supplementation during resistance training is more effective at increasing muscle strength and weightlifting performance than resistance training alone, although the response is highly variable.